Analysis of Non-volatile Organic Acids in Fermented and Dried Cocoa Beans by High Performance Liquid Chromatography - Selamat, Jinap; Dimick, P. S. (1990)
A high peiformance liquid chromatographic methodfor analysis of non-volatile acids (oxalic, citric, tartaric, succinic, malic and lactic) in fermented and dried cocoa beans is described. Bean samples were pulverized in dionized water using a Polytron Homogenizer (Brinkman)for 20 sec and centrifuged at 14000 rpm for 45 min at 25°C. The extract was alkalized to pH between 8-9 and passed through intermediate base anion exchange resin; the acidic fraction was eluted after adding 10lt/o sulphuric acid to the column. Polyphenols in the fraction were then eliminated by passing the acidic fraction through a reverse phase SEP-PAK that had been pre-wet with methanol. The eluate was analyzedfor non-volatile acids using Organic Acid Column (Bio-Rad) with O.lN H SO as a mobile phase at 65°C. The acids were detected at 214nm and quantified by comparing peak 2hezght of sample to those of standards. The method demonstrated excellent reproducibility and recoveries of the added acids.